Scar endometriosis: a rare case report - Somaiya, Hetvi; Palve, Tushar; Thatikonda, Rajashree; Kumari, Ankita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Endometriosis is a challenging topic in gynaecology, and its diagnosis necessitates a high level of suspicion, particularly when it presents at extra-pelvic sites. Extra-pelvic endometriosis, though relatively rare, can manifest in various forms, with cutaneous endometriosis being the most common. Scar endometriosis is an uncommon manifestation of endometriosis where endometrial tissue is located within the abdominal wall following a caesarean section. This case report details a 30-year-old female with scar endometriosis and reviews the current literature on its management. Scar endometriosis often poses a diagnostic challenge due to its ability to mimic other conditions, including malignancy. Accurate diagnosis requires a combination of clinical evaluation, imaging studies, and histopathological examination. Multidisciplinary approaches are crucial for effective management. This case underscores the importance of considering scar endometriosis in patients with post-caesarean section abdominal wall masses. A thorough diagnostic workup and surgical intervention are key to resolving symptoms and preventing recurrence.